Intensive Fish Farming: The Main Goals and Benefits: Budidaya Ikan Secara Intensif: Tujuan dan Manfaat Utama - Yunusov, I. (Procedia of Engineering and Life Science, 2024)
In this article, the main goals of intensive development of fisheries, efficient use of fish resources, the importance of intensive development of the fishing industry as well as use of scientifically based resource-saving methods and intensive fish farming technologies are considered. Therefore, this article is devoted to major goals and economic, social and environmental benefits of the sector in conditions of food security. Highlights: Goals: Develop fisheries, optimize fish resources, and adopt intensive technologies. Benefits: Enhance economic, social, and environmental sustainability in fisheries. Focus: Ensure food security through resource-saving, science-based fish farming methods. Keywords: fisheries productivity, intensive fisheries, fish and fish production, goals, rational use, state support, research and innovation